2016
DOI: 10.1002/2015ja022021
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamic structure of the morning high‐latitude trough region

Abstract: We describe the electrodynamics of a postmidnight, high‐latitude ionospheric trough, observed with the European Incoherent Scatter radar in northern Scandinavia on 24–25 June 2003 around 22:00–02:30 UT during quiet conditions. The UHF radar made meridian scans with a 30 min cadence resulting in nine cross sections of ionospheric parameters. The F region electric field was also determined with the tristatic system. Ionospheric equivalent currents, calculated from ground magnetometer data, mostly show an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The reason for ion temperature increase cannot be readily associated with high ion velocities in all cases because measurements of ion velocities are not reliable for all four events. Vanhamäki et al [2016] observe that for the trough on 24-25 June 2003, vertical currents are upward at the poleward side and downward in the center, where the density has the minimum, as well as on the equatorward side, which may contribute to shaping the trough. Also the deepest regions are colocated with large eastward ion velocities (more than 600 m/s in the Earth fixed frame), for at least three of the four cases (Figures 2, 4, and 8).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The reason for ion temperature increase cannot be readily associated with high ion velocities in all cases because measurements of ion velocities are not reliable for all four events. Vanhamäki et al [2016] observe that for the trough on 24-25 June 2003, vertical currents are upward at the poleward side and downward in the center, where the density has the minimum, as well as on the equatorward side, which may contribute to shaping the trough. Also the deepest regions are colocated with large eastward ion velocities (more than 600 m/s in the Earth fixed frame), for at least three of the four cases (Figures 2, 4, and 8).…”
Section: Discussionmentioning
confidence: 90%
“…Vanhamäki et al [2016] have shown that the electron density in areas of large plasma flow can be reduced by approximately a quarter, compared to the surrounding environment. Vanhamäki et al [2016] have shown that the electron density in areas of large plasma flow can be reduced by approximately a quarter, compared to the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The European Incoherent Scatter Scientific Association (EISCAT) radars can be used to derive the conductances and electric fields either at one point [e.g., Davies and Lester , ; Aikio et al , , ; Aikio and Selkälä , ] or along meridian scans [e.g., Vanhamäki et al , ]. The method of characteristics [ Amm et al , ] has been used to derive mesoscale (∼100 km) spatial distributions of FACs and conductances by combining ground magnetic measurements with electric field data from the Scandinavian Twin Auroral Radar Experiment (STARE) radar (decommissioned in 2005), with additional assumptions about the ionospheric Hall/Pedersen conductance ratio.…”
Section: Introductionmentioning
confidence: 99%